Effect of foliar nutrition and growth regulators on nutrient status and fruit quality of Eureka lemon (Citrus limon) - DEVI, KOUSHALYA; KUMAR, R; WALI, V K; BAKSHI, P; SHARMA, N; ARYA, V M (The Indian Journal of Agricultural Sciences, 2018)
Studies were conducted to standardize the doses of nutrients and growth regulators for improving the fruit quality of lemon [Citrus limon (L.) Burm.f.] cultivar Eureka while maintaining the plant nutrient status. The experiment comprised twelve foliar applications consisting of 6%, 8% and 10% potassium sulphate; 0.5%, 0.75% and 1.0% calcium chloride; 20 ppm, 30 ppm and 40 ppm 2,4-D and 20 ppm, 30 ppm, 40 ppm naphthalene acetic acid. Potassium and calcium content in leaf and fruit of Eureka lemon was influenced by foliar application of nutrients and growth regulators. Among different nutrients and growth regulators, 10% potassium sulphate and 1.0% calcium chloride reduced fruit cracking and improved the fruit quality of Eureka lemon. Maximum potassium content in leaf and fruit was recorded with foliar application of 10% potassium sulphate and maximum calcium content in leaf and fruit was recorded with the foliar sprays of 1.0% calcium chloride. Two time application of 40 ppm NAA resulted in the most effective treatment for minimizing fruit cracking and improving the fruit quality as compared to the other treatments in Eureka lemon.